PENGARUH VARIASI ARUS TERHADAP KETEBALAN LAPISAN OKSIDA DAN KECERAHAN WARNA ALUMUNIUM 6061 DENGAN METODE ANODIZING - Umar, Mega Lazuardi; Maulana, Rizki; Utomo, Rochmad Eko Prasetyaning; Wardhana, Prabuditya Bhisma Wisnu; Finali, Asmar; Yaqin, Rizki Ilmal (P3M Politeknik Negeri Indramayu, 2025)
Anodizing on aluminum aims to change the metal surface into an oxide layer so that it becomes a decorative layer, increases its hardness mechanical properties, and is resistant to corrosion. Aluminum 6061 is one of the most common types of aluminum alloy used in various industrial applications. In this research, the anodizing process was carried out using Aluminum 6061, current variations of 1, 2, and 3 amperes were chosen to determine surface characteristics including the thickness of the oxide layer, microscope macro-observations, and color brightness. The results of the experiment show that the layer oxidation thickness increases with increasing current. The results shows that the greater the current used in the anodizing process, the darker the color will be.